A measure of skewness in offense distributions - Fox, James Alan (Journal of quantitative criminology, 1988)
It has become a criminological fact of life that a small group of offenders is responsible for a far greater share of offending than its size would suggest. For example, it is well known that in the 1945 Philadelphia birth cohort, 6% of the cohort members committed 52% of the offenses. We argue, however, that the conventional percentaging approach to measuring skewness in offense distributions is inadequate. We propose and apply an alternative approach to measuring offense skewness which utilizes the offense distribution to its fullest and can easily and meaningfully be used for comparisons across or within study populations.